PRAKTEK LARANGAN MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT PADA BANK PEMERINTAH DALAM MEMBERIKAN FASILITAS SUBSIDI PERUMAHAN - putri rangkuti; T.N Syamsah; Ahmad Yani (JURNAL ILMIAH LIVING LAW, 2019)
The purpose of this research is to know and analyze the implementation and solution in monopoly practice and unfair business competition at government bank in giving facility for housing subsidy. This research uses descriptive and analytical approach, which supported by library research in order to specify this research purpose to give description about monopolistic practice in banking business in Indonesia. The results indicate that in fact, the practice of monopoly restrictions and fraudulent business competition has not run optimally and there is a fundamental weakness in it Law No. 5/1999 that mainly related to the status of implementing agencies of this law, obstacles and barriers that exist in the practical situation is the lack in implementing Law no .5 / 1999 even assessed the existence of conspiracy among banks and businessmen or other banks. Therefore there needs to be more assertive and more organized controls related to the practice of monopoly prohibition and fraudulent business competition.